2014
DOI: 10.1016/j.biomaterials.2014.04.097
|View full text |Cite
|
Sign up to set email alerts
|

The effects of confinement on neuronal growth cone morphology and velocity

Abstract: Optimizing growth cone guidance through the use of patterned substrates is important for designing regenerative substrates to aid in recovery from neuronal injury. Using laser ablation, we designed micron-scale patterns capable of confining dissociated mouse cerebellar granule neuron growth cones to channels of different widths ranging from 1.5 to 12 μm. Growth cone dynamics in these channels were observed using time lapse microscopy. Growth cone area was decreased in channels between 1.5 and 6 μm as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Our results emphasize the key role played by protruding substrate features on GC morphology occurrence and size, as reported elsewhere. , We have found that small GCs are more frequent in NT-3DFGc and NT-3DFGnc. Furthermore, the size of large, branching and re-extending GCs is significantly reduced on such substrates.…”
Section: Topography Drives Neuronal Growth Cone Establishmentsupporting
confidence: 91%
“…Our results emphasize the key role played by protruding substrate features on GC morphology occurrence and size, as reported elsewhere. , We have found that small GCs are more frequent in NT-3DFGc and NT-3DFGnc. Furthermore, the size of large, branching and re-extending GCs is significantly reduced on such substrates.…”
Section: Topography Drives Neuronal Growth Cone Establishmentsupporting
confidence: 91%
“…This competition triggers a wealth of adaptive behaviors, described in a body of work using e.g., laminin spots deposited on a PLL background [35], PLL discs surrounded by IK [36] or semaphorin 3F [37] (figure 1b-c). Smirnov et al [38] and Liu et al [39] observed a similar phenomenon when GCs confined into narrow adhesive stripes enter a node or a larger surface of spreading, respectively. Both Zhao et al [36] and Ryu et al [37], using adhesive PLL disks of increasing diameters, reported that the spreading surface of the GC tend to match those of the discs.…”
Section: Growth Cone Size Adaptation To Adhesive Surfacesmentioning
confidence: 75%
“…Beyond these systematic studies, among the fastest neurite average growth were reported for 2 µm wide stripes (i.e., 0.6 µm/min [40] as compared to the ~0.03 µm/min reported for the longest neurite on 2D PLL substrates [58 Sun, 59 Santos]). A discordant note comes however from the work of Smirnov et al, which reports no difference in the overall rate of GC advance on adhesive stripes in the range 1.5-12 µm for postnatal mice cerebellar granule neurons [38].…”
Section: Lateral Confinement 311 Adhesive Constraints On Flat Substratesmentioning
confidence: 99%
“…In support of this hypothesis, LASP1 knockdown substantially impaired the axon outgrowth and branch formation of cultured hippocampal neurons over several days. Axonal outgrowth is achieved by rapid forward movement of the growth cone interspersed with pauses and retractions ( Smirnov et al. , 2014 ).…”
Section: Discussionmentioning
confidence: 99%